Tuberculosis of sacrum mimicking as malignancy. (27th March 2012) - Shantanu, Kumar; Sharma, Vineet; Kumar, Santosh; Jain, Sonal
Abstract : Tuberculosis has always been a menace for both clinicians and radiologists due to its often non-specific and protean manifestations. Isolated tubercular involvement of sacrum is very rare. The authors present the case of a 38-year-old man with history of low-grade fever, pain and swelling in the sacral region. Skiagram revealed an osteolytic lesion of sacrum leading to the provisional diagnosis of chordoma and osteoclastoma. However, MRI was suggestive of a chronic infective condition like tuberculosis and fine needle aspiration cytology was positive for acid-fast bacilli and revealed epitheloid granulomas with caseous necrosis. Culture was positive for Mycobacterium tuberculosis . Antitubercular therapy was commenced and surgical decompression of cold abscess was done and with good clinical response. This case highlights the importance of remaining cognisant of the manifestations and the importance of considering tuberculosis as a diagnosis at unusual sites of involvement.